Integration of Rock Digital Images to Improve Carbonate Rock Physics Model of Offshore Sarawak - Lubis, L.A. (2013)
It has been recognized that carbonate reservoirs is one of the biggest reserved for hydrocarbon. Clearly, the evaluation of these reservoirs is critical. For accurate reservoir characterization and performance prediction from geophysical measurements, good understanding of geophysical response of different carbonate pore types is crucial. However, carbonate rocks is difficult to characterize due to their complex pore systems. The complex depositional environment and significant diagenesis process makes pore systems in carbonates far more complicated than in clastics. Therefore, it is difficult to establish rock physics model for carbonate rock type. In this paper, we evaluate the possible rock physics model of 20 core plugs of a Miocene carbonate platform in Central Luconia, Sarawak. The published laboratory data of this area were used as an input to create the carbonate rock physics models. The elastic properties were analyzed to examine the validity of an existing analytical carbonate rock physics model. We integrate the Xu-Payne Differential Effective Medium (DEM) Model and the elastic modulus which was simulated from a digital carbonate rock image using Finite Element Modeling. The results of this integration matched well for the separation of carbonate pore types and sonic P-wave velocity obtained from laboratory measurement. Thus, the results of this study show that the integration of rock digital image and theoretical rock physics might improve the elastic properties prediction and useful for more advance geophysical techniques (e.g. Seismic Inversion) of carbonate reservoir in Sarawak.